Pengungkapan Corporate Social Responsibility dan Reputasi Manajemen Puncak Pada Reputasi Perusahaan - Widanaputra, Anak Agung Gde Putu; Arya Widhyadanta, I Gede Dirga Surya; Ratnadi, Ni Made Dwi (Jurnal Ilmiah Akuntansi dan Bisnis, 2018)
This study aims to obtain empirical evidence of the influence of corporate social responsibility disclosure on the reputation of the company and the influence of top management reputation on the company’s reputation. The population of this study is the mining sector companies listed in BEI over the period of 2013-2016. Samples were determined by nonprobability sampling method with purposive sampling technique, obtained 116 observations. The analysis technique used is multiple linear regression. The results of the analysis show that corporate social responsibility disclosure positively affects the company’s reputation and reputation of top management positively affects the company’s reputation. The higher the corporate social responsibility disclosure index the better the company’s reputation, the better the reputation of top management reputation leads to better corporate reputation. Keywords: Corporate social responsibility disclosure, top management reputation, corporate reputation